Pronoun deletion in Hong Kong English and Colloquial Singaporean English. Issue 2 (June 2016) - SCHRÖTER, VERENA; KORTMANN, BERND
ABSTRACT: The question how substrate features and extralinguistic conditions interact in shaping contact varieties is an ongoing debate in the study of world Englishes. The present study tries to describe substrate influence by identifying an areally marked morphosyntactic feature, subject pronoun deletion, and comparing its occurrence and structural conditioning in two closely related varieties of English in Southeast Asia. Our results show that even in the typologically similar linguistic habitats of Hong Kong and Singapore, the different degrees of nativisation are reflected in the frequency and distribution of null subjects in the two relevant local varieties.